Circularly polarized luminescence of helically assembled pyrene π‐stacks on RNA and DNA duplexes. Issue 5 (9th March 2018) - Nakamura, Mitsunobu; Ota, Fuyuki; Takada, Tadao; Akagi, Kazuo; Yamana, Kazushige
Abstract: In this report, we describe the circularly polarized luminescence (CPL) of the RNA duplexes having one to four 2′‐O‐pyrene modified uridines (Upy ) and the DNA duplexes having two, four, and six pyrene modified non‐nucleosidic linkers (Py ). Both the pyrene π‐stack arrays formed on the RNA and DNA double helical structures exhibited pyrene excimer fluorescence. In the pyrene‐modified RNA systems, the RNA duplex having fourUpy s gives CPL emission with glum value of <0.01 at 480 nm. The structure of pyrene stacks on the RNA duplex may be rigidly regulated with increase in theUpy domains, which resulted in the CPL emission. In the DNA systems, the pyrene‐modified duplexes containing two and fourPys exhibited CPL emission with glum values of <0.001 at 505 nm. The pyrene π‐stack arrays presented here show CPL emission. However, the glum values are relatively small when compared with our previous system consisting of the pyrene‐zipper arrays on RNA. Abstract :